Impregnation of Fe3+ into MCM-41 Pores: Effect of Fe3+ Concentration on the Weight Percent of Fe-Frameworks and Fe-Non-Frameworks - Suyanta Suyanta; Agus Kuncaka; Mudasir Mudasir (Indonesian Journal of Chemistry, 2023)
Silica from rice husks (RH) has been used as a starting ingredient in the sonication synthesis of MCM-41 (RH-MCM-41). The impregnation of Fe3+ into RH-MCM-41 pores to produce RH-MCM-41 containing Fe2O3 and Fe (denoted as Fe2O3-Fe-RH-MCM-41) was carried out by examining the effect of various Fe3+ concentrations on the weight percent of Fe-frameworks (Fe3+ that replaces Si4+ in silicate frameworks) and Fe-non-frameworks, i.e., the iron oxide formed outside the silicate frameworks. Fe2O3-Fe-RH-MCM-41 was washed with a 0.01 M HCl solution to remove Fe-non-frameworks from the materials and give Fe-RH-MCM-41 containing Fe-frameworks. The Fe content in Fe2O3-Fe-RH-MCM-41 (Fe-total) and Fe-RH-MCM-41 (Fe-frameworks) for each sample was determined by an AAS (atomic absorption spectrometer), whereas the content of Fe-non-frameworks was calculated from the difference between Fe-total and Fe-frameworks. The XRD (X-ray diffraction) pattern, N2 adsorption-desorption isotherm profile, as well as the TEM (transmission electron microscope) image clearly demonstrate that the RH-MCM-41 exhibits an ordered p6mm hexagonal mesostructure with a large specific surface area and uniform pore size. Based on the weight percents of Fe-frameworks found in each sample, it is clear that the content of Fe-non-frameworks is significantly enhanced compared to that of Fe-frameworks when the more concentrated Fe3+ is used.